Characteristics of Neonatal Abstinence Syndrome (NAS) in a rural clinic population: Tracking with Electronic Medical Health Records (EHR) - Jill D Cochran; Traci Jarrett; Adam Baus (Rural Nurse Organization; Binghamton University, 2020)
Purpose The impact of intrauterine exposure of opioids and other addictive substances on pediatric patients is concerning for health care providers in rural WV. NAS patients must be identified, screened, and treated during the pediatric years to facilitate improved outcomes. The purpose of this research was to evaluate the ability of rural providers to use EHRs to identify, describe, and monitor aspects of NAS across the pediatric health span. Methods The research team used de-identified data of patients that had the NAS diagnosis from a rural clinic. One hundred fifty-five charts were evaluated. Demographics, clinical characteristics, and developmental milestone status were extracted from charts. Results There were differences in characteristics across age groups. Reported secondhand smoke was higher among the 0-3 year olds. Normal BMI percentile was highest among 4-5 year olds. The Ages and Stages Developmental screening was abnormal more in those aged 6-19 years. Foster care was highest among the ages 0-3 years. The 4-12 age groups highest amount of no show visits. Respiratory illness was the most frequent diagnosis and was highest in the 4-5 age group. Eye and ear diagnosis were noted as a recurrent diagnosis in the 4-5 year old group. Diagnosis related to mental health were highest in the 6-18 age group. Discussion The EHR can be used to describe and track special populations such as NAS in rural areas. Tagging and tacking patients with NAS can help primary care providers manage care and anticipate age related health care needs. Tracking high risk populations assures that the patient care is maintained. Tracking no show rates assists providers in assuring that patient's caregivers are compliant in necessary treatments and referrals. Child Protection can also be involved if medical neglect is noted. EHRs are useful in identifying high risk populations such as NAS to facilitate treatments and continuity of care. DOI: http://doi.org/10.14574/ojrnhc.v20i2.625